Métaphores dans le lexique, français et polonais, de l'hydrologie - Kozar, Liliana (Wydawnictwo Naukowe UAM, 2008)
Metaphor has been one of the most important research areas in linguistics for a few decades up to now. However, its value as a way of artistic expression in general language is indisputable, its presence in the specialised languages may be strongly questionable. How to explain the success of metaphor among the terms? What is its type and function? What is the mechanism of the meaning and the direction of metaphorisation in the language of hydrology, French and Polish? There are some questions to which the author of this paper attempted to find answers.
Metaphors in Polish and French terminology of hydrology field
Keywords: Metaphors; Language of hydrology; French language; Polish language